Education Expenditure in Punjab and Haryana : An Empirical Analysis - Tomar, Reeta (Arthshastra Indian Journal of Economics & Research, 2017)
Education is the backbone of a country. Against this background, this paper analyzed the pattern of education expenditure by the state governments of Punjab and Haryana from 1990-2013. Also, the pattern of intra-sectoral allocation of education expenditure on elementary education, secondary education, university and higher education, and technical education was analyzed. Next, the pattern of expenditure on elementary education, secondary education, university and higher education, and technical education was analyzed with respect to education budget, state budget, and state income (NSDP) in both the states. The main findings showed that in both the states, total education expenditure and expenditure on major heads of education had increased in absolute terms during the study period, but as a percent of state education budget, state budget, and state income declined. Education budget of both these states was around 2% of the state income, which was much lower than the recommended 6% of state income. The Central Advisory Board of Education (CABE) Committee in 2005 suggested that at least 3% of state income be allocated to elementary education, 1.5% to secondary education, 1% to higher education, and 0.5% to technical education, but none of these states were found to be near to these recommendations.